2021
DOI: 10.1002/ar.24585
|View full text |Cite
|
Sign up to set email alerts
|

The so‐called foramen singulare in cetacean periotics is actually the superior vestibular area

Abstract: It is nearly 100 years ago that the “foramen singulare” was first identified in cetacean periotics. Since then, the “foramen singulare” has been recognized in periotics of many cetacean species, extant or extinct. Surprisingly, however, it has never been confirmed if the foramen singulare in cetacean periotics is really homologous to that in other mammals. It is known that in mammals including humans the posterior ampullary nerve, which innervates the posterior semicircular duct, passes through the foramen sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Thus, turtle endocasts are relatively poor predictors of brain morphology (Edinger, 1929;Evers et al, 2019;Ferreira et al, 2022;Mautner et al, 2017;Paulina-Carabajal et al, 2013;Wyneken, 2001;Zangerl, 1960). This pattern also holds in certain other vertebrate taxa in which the brain volume does not fill most of the endocranial space, such as squamates (Allemand et al, 2023) and cetaceans (Boessenecker et al, 2017;Ichishima, Kawabe, & Sawamura, 2021;Racicot, 2022), but differs from the relatively good reflection of brain shape by endocast shape in archosaurs (Iwaniuk & Nelson, 2002;Watanabe et al, 2019), many mammals (e.g., De Miguel & Henneberg, 1998Haight & Nelson, 1987;Jerison, 1973;Macrini et al, 2007), and amphibians (Clement et al, 2021). In taxa for which the brain-to-endocranial cavity index is low, the endocast tends to be more cylindrical than the underlying brain (Hopson, 1979;Jerison, 1973;Watanabe et al, 2019).…”
Section: Neuroanatomymentioning
confidence: 89%
“…Thus, turtle endocasts are relatively poor predictors of brain morphology (Edinger, 1929;Evers et al, 2019;Ferreira et al, 2022;Mautner et al, 2017;Paulina-Carabajal et al, 2013;Wyneken, 2001;Zangerl, 1960). This pattern also holds in certain other vertebrate taxa in which the brain volume does not fill most of the endocranial space, such as squamates (Allemand et al, 2023) and cetaceans (Boessenecker et al, 2017;Ichishima, Kawabe, & Sawamura, 2021;Racicot, 2022), but differs from the relatively good reflection of brain shape by endocast shape in archosaurs (Iwaniuk & Nelson, 2002;Watanabe et al, 2019), many mammals (e.g., De Miguel & Henneberg, 1998Haight & Nelson, 1987;Jerison, 1973;Macrini et al, 2007), and amphibians (Clement et al, 2021). In taxa for which the brain-to-endocranial cavity index is low, the endocast tends to be more cylindrical than the underlying brain (Hopson, 1979;Jerison, 1973;Watanabe et al, 2019).…”
Section: Neuroanatomymentioning
confidence: 89%
“…Although the impact of size differences of the different vestibular nerve branches to cetacean senses are yet to be determined, an intriguing study incorporating μCT along with iodine staining found that what was once known as the "foramen singulare" in cetacean periotics is actually the "superior vestibular area" (Ichishima et al, 2021). This work is a great example of a comparative analysis effectively incorporating new methods in CT to clarify homologies.…”
Section: Ontogenetic Development Of Sensory Anatomymentioning
confidence: 84%
“…The ontogenetic development of cetaceans is an area where aspects of sensory system evolution can be further examined, and where inroads have been made using nondestructive imaging (Frainer et al, 2019;Ichishima, Kawabe, & Sawamura, 2021;Lanzetti, 2019;Lanzetti, Berta, & Ekdale, 2018;Thean, Kardjilov, & Asher, 2017;Yamato & Pyenson, 2015). The measurement techniques described above for the inner ear and brain can equally be applied to developing fetuses.…”
Section: Ontogenetic Development Of Sensory Anatomymentioning
confidence: 99%
“…All specimens are now housed in the Cenozoic Palaeontology Collections at Iziko South African Museum (SAM). Anatomical terminology follows Mead and Fordyce (2009) and Ichishima et al (2021). 1) and marked by a somewhat squared anterior border with a weakly developed anterolateral shelf.…”
Section: Methodsmentioning
confidence: 99%